STRATEGI PEMBELAJARAN BERBASIS DISKUSI DALAM KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Regina Sipayung; Saragih, Elly Saprida; Ronauli Fransiani Sinaga; Agita Jesilia Br Sembiring; Elovani Marbun; Benediktus; Kristin Monika Berbi Sirait; Fatricia Cahyati Manullang; Sepia Tumanggor; Fitri Hannayani O Simatupang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of disciplined character is one of the primary goals of elementary education because it helps students develop responsibility, self-control, and compliance with school rules. However, many elementary school students still demonstrate low levels of discipline, including arriving late to school, violating school regulations, and showing limited responsibility in completing academic tasks. These conditions highlight the need to optimize guidance and counseling services as an effective strategy for fostering students' disciplinary character. This study aimed to describe the role of guidance and counseling services in developing the disciplinary character of elementary school students. The research employed a qualitative approach using a library research method. Data were collected from various scholarly sources, including books, journal articles, and relevant documents, and were analyzed through descriptive analysis involving data collection, data reduction, data presentation, and conclusion drawing. The findings indicate that guidance and counseling services contribute significantly to the development of students' disciplinary character through individual guidance, group guidance, classroom guidance, habituation of disciplined behavior, teacher role modeling, motivational reinforcement, and collaboration between schools and parents. The success of disciplinary character development is supported by consistent counseling implementation, parental involvement, and a positive school environment. Therefore, guidance and counseling services represent an effective and sustainable strategy for developing disciplinary character among elementary school students.